Physicothermal and Topography Analysis of Polyurethane Modified Bitumen with Rediset for WMA Application - Faridah Hanim Khairuddin; Siti Zubaidah Mohd Asri; Noor Aina Misnon; Nur Izzi Md Yusoff; Auni Diyana Fadzil; Ku Zarina Ku Ahmad (Journal of Engineering and Technological Sciences, 2023)
The effects of modifying a 60/70 penetration grade bitumen with 3 wt% polyurethane (PU) and a Warm Mix Asphalt (WMA) additive, namely Rediset, were explored in this research. Penetration, softening point, viscosity, and ductility tests were employed for consistency testing, while the differential scanning calorimetry was used for thermal characterization. The topography and surface roughness of the modified bitumen were evaluated using atomic force microscopy. Adding PU and Rediset to the base bitumen (BB) stiffens the BB slightly, giving it a lower penetration and higher viscosity values, which improves the rutting resistance. The thermal transition of the glass temperature and melting temperature are similar to the BB. Furthermore, the addition of PU and Rediset to BB shows a clear bee structure topography in dry condition, indicating better dispersion, while in wet condition, the bee structure is mostly affected in the catana and para phase that reveals a reduced in the the wax content of the BB. The bitumen modified with PU and Rediset has a lower surface roughness than BB, making it less susceptible to moisture damage.